Pengaruh Modal Asing Terhadap Kinerja Keuangan (Studi kasus Pada PT. Karya Mandiri Di Bandar Lampung) - Habiburrahman HABIBURRAHMAN; Panji Adi Laksana; Haninun HANINUN (Jurnal Akuntansi dan Keuangan, 2011)
The purpose of this study was to determine the effect of increasing foreign equity to the level of liquidity, solvency and profitability of the company and to determine the trend of the use of foreign capital and the development of liquidity, solvency and profitability. Based on the analysis we concluded that the terms of the current ratio is seen to increase liquidity shows that the increase in current liabilities sector followed by an increase in current assets sector, but if dilikat quick ratio is low, it can be said that the company is too much to invest in inventory. Similarly, if viewed from a low cash ratio indicates that the amount of cash money supply too little or small company when compared to the amount of current debt. Where a moment and ask the creditor to collect the debt payments difficult to meet these obligations, from 2004 to 2006 ratio calculations showed that the decrease in security of the rights of creditors. This is indicated by the decline in the company's solvency ratio of total assets to debt ratio, net worth to debt ratio, proprietory ratio and net worth to debt ratio. This means that the company is in a state insolvabel means the company can not immediately meet long-term financial liabilities if the company is liquidated. Therefore the company improve its capital structure so as to increase the solvency and profitability of the terms of the use of foreign capital to increase profitability. This is due to the large amount of foreign capital invested in the company. Then the company will be able to expand its business, until the target profit (profit) is expected to be achieved due to the amount of capital is in the company increases.